Progress and Perspective of CRISPR‐Cas9 Technology in Translational Medicine - Ruixuan Zheng; Lexiang Zhang; Rokshana Parvin; Lihuang Su; Junjie Chi; Keqing Shi; Fangfu Ye; Xiaoying Huang (Advanced Science, 2023)
Abstract Translational medicine aims to improve human health by exploring potential treatment methods developed during basic scientific research and applying them to the treatment of patients in clinical settings. The advanced perceptions of gene functions have remarkably revolutionized clinical treatment strategies for target agents. However, the progress in gene editing therapy has been hindered due to the severe off‐target effects and limited editing sites. Fortunately, the development in the clustered regularly interspaced short palindromic repeats associated protein 9 (CRISPR‐Cas9) system has renewed hope for gene therapy field. The CRISPR‐Cas9 system can fulfill various simple or complex purposes, including gene knockout, knock‐in, activation, interference, base editing, and sequence detection. Accordingly, the CRISPR‐Cas9 system is adaptable to translational medicine, which calls for the alteration of genomic sequences. This review aims to present the latest CRISPR‐Cas9 technology achievements and prospect to translational medicine advances. The principle and characterization of the CRISPR‐Cas9 system are firstly introduced. The authors then focus on recent pre‐clinical and clinical research directions, including the construction of disease models, disease‐related gene screening and regulation, and disease treatment and diagnosis for multiple refractory diseases. Finally, some clinical challenges including off‐target effects, in vivo vectors, and ethical problems, and future perspective are also discussed.